MySQL Admin Cookbook - Schneller, Daniel (Packt Publishing, 2011)
This book uses the approach of a cookbook, presenting solutions to problems in the form of recipes. Each recipe provides the reader with easy step-by-step descriptions of the actions necessary to accomplish a specific task. Example values and code samples are used throughout the recipes, which makes adaptation for individual needs easy.Administrators of all skill-levels will find step-by-step instructions for practical approaches to MySQL configuration, maintenance, and optimization topics. Each recipe uses a concrete example for easy understanding. This book is for ambitious MySQL users as well as professional data center database administrators. Beginners as well as experienced administrators will profit from this cookbook and get fresh ideas to improve their MySQL environments. Detailed background information will enable them to widen their MySQL horizon.It does not cover SQL basics, how to install MySQL servers, or how to design a relational database schema. Readers are expected to have a basic understanding of the SQL language and database concepts in general.